Perfectionism and coping with injury in marathon runners: A test of the 2×2 model of perfectionism - Jowett, G. E.; Hill, A. P.; Forsdyke, D.; Gledhill, A. (Psychology of Sport and Exercise, 2018)
Previous research has found perfectionism dimensions to predict coping strategies in sport when dealing with various stressors. We aimed to extend previous research by examining the interactive effects of perfectionism dimensions on strategies employed by marathon runners to cope with injury. This involved testing the hypotheses of the 2×2 model of perfectionism in marathon runners. Marathon runners (n=224, female n=81, M age=39.77 years, SD=9.50 years) completed measures capturing four subtypes of perfectionism (pure self-oriented perfectionism, pure socially prescribed perfectionism, mixed perfectionism, and non-perfectionism) and strategies for coping with injury (problem-focused coping, emotion-focused coping, and avoidance coping). Moderated regression analyses provided support for all four hypotheses of the 2×2 model for problem-focused coping, one hypothesis for emotion-focused coping, and none for avoidance-coping. Problem-focused coping was highest for pure self-oriented perfectionism and lowest for pure socially prescribed perfectionism. Emotion-focused coping was higher for pure self-oriented perfectionism compared to non-perfectionism. Finally, avoidance coping was similar across all subtypes. The results provide initial evidence that the 2×2 model of perfectionism explains differences in the use of coping strategies in context of marathon running injury.